Localizing a metabolic focus during a functional seizure with fluorodeoxyglucose positron emission tomography-computed tomography - Mirzaei, Siroos; Preitler, Barbara; Wenzel, Thomas (World Journal of Nuclear Medicine, 2021)
Traumatic brain injuries can lead to long-term mental seizures that are difficult to differentiate from dissociative psychogenic symptoms, respectively, psychogenic nonepileptic seizures. Recent articles have drawn attention to the need of differentiation of psychological and brain trauma-related symptoms in survivors of violence. This case study reflects a diagnostic step in a 20-year-male who reported to have been subjected to torture, including blunt force to the head 2 years before examination. He suffers from episodical headaches followed by mental bouts of aggression and restlessness. We performed a brain 18F-fluorodeoxyglucose positron emission tomography (PET)-computed tomography to identify a cerebral correlate of the psychogenic seizures. The examination yielded a hypermetabolic focus in the frontal superior parasagittal region. Psychogenic seizures can frequently be observed as culture-specific “idioms of distress” and can challenge diagnostic evaluation, especially in the victims of violence with an additional history of blunt brain trauma. The advances in molecular imaging such as PET can be expected to play a crucial role in forensic and clinical assessment in the increasing number of such patients.
Keywords: Brain imaging; fluorodeoxyglucose positron emission tomography; functional seizures; posttraumatic stress disorder; torture